Survey of training needs on archives administration for records personnel and archivists in the local government units in Region I - Rey, Emma C. Munoz 1953-
The descriptive survey method of research with questionnaires as data-gathering tool was used. Two sets of questionnaires, one for records personnel and archivists and one for human resource development officers were either sent by mailed or personally administered. Data were gathered from the second week of February to the whole month of April.